Analysis of Students' Creative Thinking Levels in Rhythmic Gymnastics Learning - Yonifia Anjanika; Atri Widowati; Sugih Suhartini; Fitri Diana; Grafittie Decheline (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to look at the creative thinking level of Sentolo 4 Middle School students, Kulonprogo Yogyakarta, in rhythmic gymnastics learning where the characteristics of the class students should be included in the operational cognitive development stage of the format. At this stage, children or students can handle hypothetical situations and their thinking processes are no longer dependent on things that are real and have logical reasoning, which can generate ideas. Also able to think logically, think with formal theoretical thinking based on propositions, and be able to conclude. The sample in this study was 58 students of class VII and VIII (30 students of class VII and 28 students of class VIII) at SMP 4 Sentolo, Kulonprogo Yogyakarta. The instrument used was in the form of essay questions which were distributed to the samples with a total of 22 questions consisting of 10 fluency thinking or problem solving questions, and 12 flexible thinking questions. The results obtained are that students who are in the Very Creative, Creative, and Quite Creative categories can only be drawn into conclusions, namely in class VII there are 24 students (80%), and in-class VIII there are 21 students (85, 71%), it can be said that these students have fulfilled the indicators of flexible thinking and fluency thinking in other words as a whole in the Creative category.